Elderly People Health Monitoring System by Using IoT - Hairozaman, Sharmine; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2022)
IoT-based Health Monitoring systems have emerged as a hot topic and critical research area today. Nowadays, the elderly face serious health problems as a result of inadequate health monitoring. Technologies to monitor their activities at home must be strengthened. Elderly people are frequently left home alone because their children work or live far away. As a result, many people struggle to keep track of them consistently. This project aims to build an Internet of Things Health Monitoring System that uses the ESP8266 ESP-01 for IoT wireless data transmission via the Blynk application’s Android platform. For the healthiest elderly people, resting heart rates range from 60 to 100 beats per minute. Therefore, the result that gets for the pulse sensor is accurate. Furthermore, the average DS18B20 temperature sensor does not show significant differences between the body thermometer and temperature sensor (DS18B20). As a result, the DS18B20 temperature sensor can be used to take body temperature readings. The elderly people’s data records are kept for an extended time. The information is saved with the help of an Android app that controls the app’s device. When the temperature or pulse sensor is beyond in critical state, the alert will appear in the smartphone and send a notification to the email. The data of elderly people also can convert to excel with the date and time. This proposed system allows elderly and chronically ill patients to live independently in their own homes with care facilities while feeling secure in the knowledge that they could be being monitored.